The crime of my very existence : Nazism and the myth of Jewish criminality - Berkowitz, Michael 1959- (The S. Mark Taper Foundation imprint in Jewish studies, 2007)
Above suspicion? : facts, myths, and lies about Jews and crime -- The construction of "Jewish criminality" in Nazi Germany -- The self-fulfilling prophecy of the ghettos -- Inverting the innocent and the criminal in concentration camps -- Re-presenting Zionism as the apex of global conspiracy -- Lingering stereotypes and Jewish displaced persons -- Jewish DPs confronting the law : prescriptions, self-perceptions, and pride of self-control